2019
DOI: 10.1039/c9ra07176h
|View full text |Cite|
|
Sign up to set email alerts
|

Icariin enhances intestinal barrier function by inhibiting NF-κB signaling pathways and modulating gut microbiota in a piglet model

Abstract: This study investigated the effects of icariin on intestinal barrier function and its underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…The intestinal epithelial barrier includes a lining of enterocytes and intercellular multiprotein complexes (such as ZO-1, claudin and occludin), which plays a crucial role in preventing pathogenic bacteria, antigens and toxins from entering into the systemic circulation via the gut lumen( Chen et al., 2018 ; Li et al., 2019 ). The DAO, D-lactate and endotoxins in serum are useful markers of intestinal permeability ( Xiong et al., 2019 ). The present study showed that WB supplementation reduced the serum DAO activity compared with CON on d 14, suggesting decreased intestinal permeability and enhanced intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal epithelial barrier includes a lining of enterocytes and intercellular multiprotein complexes (such as ZO-1, claudin and occludin), which plays a crucial role in preventing pathogenic bacteria, antigens and toxins from entering into the systemic circulation via the gut lumen( Chen et al., 2018 ; Li et al., 2019 ). The DAO, D-lactate and endotoxins in serum are useful markers of intestinal permeability ( Xiong et al., 2019 ). The present study showed that WB supplementation reduced the serum DAO activity compared with CON on d 14, suggesting decreased intestinal permeability and enhanced intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal microbiota is a complicated ecosystem that has a significant impact on gastrointestinal function, immune function, and health of the host ( Xiong et al., 2019 ). Alpha-diversity is defined as the diversity of organisms within one site or one sample.…”
Section: Discussionmentioning
confidence: 99%
“…Weaning stress could induce imperfect and impaired gastrointestinal tract, which is associated with increased permeability, resulting in translocation of pathogens through the intestinal epithelial cells into systemic circulation [8]. DAO, endotoxin and D-lactate are intestinal permeability-related biomarkers and their levels in serum could re ect the intestinal barrier function [35]. In this study, HWP increased serum DAO concentration on day 28 compared with ESBM, indicating that piglets in the ESBM group had better intestinal barrier function.…”
Section: Discussionmentioning
confidence: 58%
“…Weaning process leads to intestinal in ammation and promotes the release of pro-in ammatory cytokines, which can explain the stunted growth performance and intestinal disorders of piglets [36]. Numerous pro-in ammatory cytokines including IL-1β, IL-6, and TNF-α are involved in the regulation of the in ammatory response and their levels could re ect the in ammatory status in the body [35]. Our result showed that ESBM decreased serum levels of IL-1β and IL-6 compared with HWP and FSBM, indicating that ESBM was superior to HWP and FSBM in alleviating weaning stress-induced in ammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intestinal in ammation is closely associated with the intestinal barrier. IL-1β, IL-6 and IL-8 were reported to impair intestinal barrier function by rearranging tight junction proteins, while TNF-α signi cantly disrupts the tight junctions between intestinal epithelial cells 48 . Hence, GOS alleviated the colonic in ammation caused by LPS challenge in piglets, which contributed to the maintenance of colonic mucosal barrier function.…”
Section: Discussionmentioning
confidence: 99%